Electrical Troubleshooting: Week 3 Materials - Ken Dickson-Self (2018)
This course provides an introduction into electrical troubleshooting theory in troubleshooting common electrical problems including: low voltage, high voltage, unwanted resistance, open circuits, high resistance shorts-to-ground, and current and voltage unbalance. Efficiency technology and sustainable practices are covered. An effective troubleshooting methodology is embedded in this course.